Efecto de un bioestimulante y un biorremediador del suelo sobre la producción y calidad del forraje brachiaria brizantha cv. Mg 5 en un sistema de producción de ganado de carne en Florencia, San Carlos, Alajuela, Costa Rica - Delgado-Rodríguez, Sofía (Instituto Tecnológico de Costa Rica, 2019)
The main objective of the present investigation was to evaluate the effect of a biostimulant (Grain Set®) and a soil bioremediator (Soil Set®) on the production and quality of the forage Brachiaria brizantha cv. MG 5 in a beef cattle production system, in addition, to also evaluate its effect on the biological activity of the soil where the trial was located. It was carried out at Finca Las Nubes, located in Florencia, San Carlos, Alajuela, Costa Rica. For the development of the research four treatments were used, with four repetitions, for a total of sixteen experimental units, which were established in an area of 1,137 ha, during six months with a sampling per month, using an experimental design of Complete Blocks at random with factorial arrangement. The variables evaluated were dry biomass, dry matter, crude protein, neutral detergent fiber and acid detergent fiber, in addition to the biological activity of the soil. The data were subjected to analysis of variance and a multiple comparison test between the treatments, in addition they were analyzed between samples. In the same way, a correlation was made with three climatic variables (precipitation, temperature and relative humidity). The results showed that in terms of the productive variable (dry biomass) and biological activity, there were significant differences (p-value <0.05) in the Soil Set® treatment, in the quality variables (dry matter, crude protein, fiber neutral detergent and acid detergent fiber) there were no significant differences between treatments (p-value> 0.05); no correlation was found between the climatic variables with the effect of Grain Set® and Soil Set® on the productive and quality variables studied. It was concluded that, with the use of the products, alone or together, it is possible to increase the number of animals that can be fed per hectare under the evaluated farm conditions.
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2019.
Keywords: Producción agropecuaria; Producción animal; Propiedades del suelo; Variabilidad climática; Uso del suelo; Agricultura; Agronomía; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING